Pemanfaatan Media Sosial dalam Meningkatkan Kinerja UMKM Menurut Perspektif Ekonomi Islam di Usaha Terang Bulan Legend Sidoarjo - Anggraeni, Silvia Abni; Rahman, Taufiqur (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The use of social media has become a significant phenomenon in the business world, including Micro, Small and Medium Enterprises (UMKM). This article reviews how social media can improve the performance of UMKM from an Islamic economic perspective, with the Case Study of Terang Bulan Legend in Sidoarjo. First, social media gives UMKM wider access to market their products and services. This is in line with Islamic economic principles which encourage transparency and healthy competition in the market. With social media, UMKM can reach more consumers without having to incur large costs. Second, social media allows UMKM to build better relationships with their customers. In an Islamic economic perspective, building strong and mutually beneficial relationships with customers is highly valued. Social media facilitates more intensive interaction between UMKM and customers, thereby increasing customer loyalty. Third, social media makes it easier for UMKM to monitor market trends and consumer needs. By adhering to Islamic economic principles, UMKM can adapt more quickly to market changes and ensure their products and services remain relevant. In the Terang Bulan Legend Case Study in Sidoarjo, the use of social media has resulted in a significant increase in sales and profits. This is concrete evidence that social media can help MSMEs improve their performance, in accordance with Islamic economic principles that encourage fair and sustainable business. In conclusion, the use of social media in UMKM, such as Terang Bulan Legend in Sidoarjo, has a positive impact that is in line with Islamic economic principles. Social media helps UMKM expand their markets, build strong customer relationships, and stay competitive in an ever-changing market. All of this contributes to improving the economic and social performance of UMKM. Keywords: Social Media, UMKM, Islamic Economics